ASSESSMENT OF EFFICIENCY OF COMPOST PREPARED FROM ANIMAL WASTE IN THE REDUCTION OF TOTAL PETROLEUM HYDROCARBON IN CRUDE OIL IMPACTED SOIL - ADEBOLA ADEKUNLE; IHEOMA ADEKUNLE; SUHAIB AROGUNDADE (Journal of Engineering Studies and Research)
The aim of this study was to investigate the potentials of composted animal waste in biodegradation of hydrocarbon in a cost-effective, efficient, and environmental-friendly manner. The contaminated soil sample was collected from Ojoo area in Ibadan, Oyo state, Nigeria. Two different types of compost – sheep-waste-sawdust (SPW-SD) and goat-waste-sawdust (GTW-SD) were applied to a soil at a rate (0 g, 750 g, 450 g). The result depicted that the contaminated soil experienced an enhanced natural bioremediation due to the applied bioremediation agents and the contaminated soil treated with SPW-SD gave best results. Samples remediated with SPW-SD and GTW-SD showed a Total Petroleum Hydrocarbon (TPH) removal efficiency of 55.4% and 7.9% respectively. Analysis showed that oil type, compost rate and period of application influenced the bioremediation process. From the results, composted organic waste application is a good and efficient way of remediating hydrocarbon impacted soil.